Antiplasmodial Natural Products - Nogueira, Claudio R. [UNESP]; Lopes, Lucia Maria Xavier [UNESP] (Mdpi Ag, 2011)
Malaria is a human infectious disease that is caused by four species of Plasmodium. It is responsible for more than 1 million deaths per year. Natural products contain a great variety of chemical structures and have been screened for antiplasmodial activity as potential sources of new antimalarial drugs. This review highlights studies on natural products with antimalarial and antiplasmodial activity reported in the literature from January 2009 to November 2010. A total of 360 antiplasmodial natural products comprised of terpenes, including iridoids, sesquiterpenes, diterpenes, terpenoid benzoquinones, steroids, quassinoids, limonoids, curcubitacins, and lanostanes; flavonoids; alkaloids; peptides; phenylalkanoids; xanthones; naphthopyrones; polyketides, including halenaquinones, peroxides, polyacetylenes, and resorcylic acids; depsidones; benzophenones; macrolides; and miscellaneous compounds, including halogenated compounds and chromenes are listed in this review.
Keywords: malaria; antimalarial; antiplasmodial; Plasmodium